2016
DOI: 10.17261/pressacademia.2016219940
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Environmental Consumption: Is It Really All About the Environment

Abstract: This study investigates the impact of corporate governance and foreign ownership on the flow of firm-specific information to stock prices in Turkey. This study contributes to the existing literature by examining the relation between governance, ownership and stock price synchronicity that describes firm level information asymmetry and transparency in Turkey. We examine the effects of CEO duality, board independence, board size and foreign ownership on the amount of firm-specific information incorporated into s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 152 publications
0
17
0
Order By: Relevance
“…In Indonesia, researchers like Julina [33] upheld that environmental awareness can influence individual attitude, which will translate into performing a green culture. Research conducted by Paul et al [34], and Koksal and Tuger [35] found that environmental awareness influences environmental attitude. In Malaysia, the study of Aman et al [36] rejects the influence of environmental awareness on environmental attitude, and the studies of Levine [37], Hartmann and Apaolaza-Ibazez [38] shows no sign.…”
Section: Green Environmental Awarenessmentioning
confidence: 98%
“…In Indonesia, researchers like Julina [33] upheld that environmental awareness can influence individual attitude, which will translate into performing a green culture. Research conducted by Paul et al [34], and Koksal and Tuger [35] found that environmental awareness influences environmental attitude. In Malaysia, the study of Aman et al [36] rejects the influence of environmental awareness on environmental attitude, and the studies of Levine [37], Hartmann and Apaolaza-Ibazez [38] shows no sign.…”
Section: Green Environmental Awarenessmentioning
confidence: 98%
“…PEB was measured using a 10-statement scale including 3-R activities (reduce-recycle-reuse) and green buying decisions. The 10 statements were adapted from the study carried out by Cleveland et al (2005), Trivedi et al (2015) and Dursun et al (2016): “I switch off the lights in the rooms that are not being used,” “I close the water tap while I do my dish washing,” “I close the water tap while brushing my teeth,” “I sort soda cans for recycling,” “I sort papers and cardboard for recycling,” “I sort glass containers for recycling,” “I reuse the backside of printed sheets as draft paper,” “I buy fruit and vegetables grown without pesticides or chemicals,” “I buy paper products that are made from recycled materials” and “I buy household detergents and cleaning solutions that are environmentally friendly.” Respondents rated each item using a 10-point Likert-type scale (1 = never do it to 10 = always do it ).…”
Section: Research Context Data Collection and Methodsmentioning
confidence: 99%
“…For example, Nezakati et al (2014) selected the TPB to build a model aimed to investigate the intention to purchase green products; Al Mamun et al (2018) propose a model derived from the TPB model to explain both willingness to pay for environmentally friendly products and payment behavior for environmentally friendly products. Parallel to this, we find several investigations into pro-environmental intentions, exploring the effect of specific factors based on context-specific models: Han et al (2011) investigated whether personal attitudes (i.e., regarding severity of environmental problems, inconvenience of being environmentally friendly, importance of being environmentally friendly, and level of responsibility of business corporations) affect the intentions to pay more for a green hotel; Trivedi et al (2015) proposed a model in which willingness to pay for environmentally friendly products is explained by PEB and environmental locus of control; Biswas (2016) investigates the association and interaction of consumers’ perceptual or behavioral factors, external contextual factors, and responsiveness to corporate environmental performance on willingness to pay price premium for green products; Dursun et al (2016) examines the predictive power of six self-determined motivational types and value orientations to two types of pro-environmental intentions—preference for a high environmental performance car and intention to donate to an environmental organization; Sang et al (2020) developed a research model to explain the influencing factors of consumers’ willingness to purchase green housing.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the research on responsible consumption, sustainable consumption, and green marketing in the Turkish context has intensified with several foci. Because the literature is mainly originating from marketing, economy, and finance fields, the research topics are mostly related to the factors that affect purchase decisions, such as the different theoretical explanations of pro‐environmental behaviors, the effects of personal values on sustainable consumption, environmental consumption decisions (Ay, 2017; Dursun, Kabadayi, Köksal, & Tuger, 2016), and evaluation methods of sustainable consumption behaviors (Dogan, Bulut, & Çimrin, 2015; Dursun, Kabadayı, & Tuğer, 2018).…”
Section: The Turkish Context: From Green Consumerism To Swap Eventsmentioning
confidence: 99%